2009
DOI: 10.1158/1940-6207.capr-09-0031
|View full text |Cite
|
Sign up to set email alerts
|

A Pooled Analysis of Continued Prophylactic Efficacy of Quadrivalent Human Papillomavirus (Types 6/11/16/18) Vaccine against High-grade Cervical and External Genital Lesions

Abstract: Quadrivalent human papillomavirus (HPV) vaccine has been shown to provide protection from HPV 6/11/16/18-related cervical, vaginal, and vulvar disease through 3 years. We provide an update on the efficacy of the quadrivalent HPV vaccine against high-grade cervical, vaginal, and vulvar lesions based on end-of-study data from three clinical trials. Additionally, we stratify vaccine efficacy by several baseline characteristics, including age, smoking status, and Papanicolaou (Pap) test results. A total of 18,174 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 281 publications
(142 citation statements)
references
References 24 publications
2
135
0
5
Order By: Relevance
“…We found that the majority of physicians in all specialties, except OB-GYNs, reported that the HPV vaccine was effective in preventing cervical cancer alone (60%-68%). Despite increasing evidence demonstrating that the HPV vaccine confers protection against vaginal, vulvar, and anal cancers, [3][4][5][6] most physicians in this survey were unaware of this additional protection. OB-GYNs were the best informed, with identification of noncervical cancer protection at least twice as often as other specialties, which is consistent with prior research.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the majority of physicians in all specialties, except OB-GYNs, reported that the HPV vaccine was effective in preventing cervical cancer alone (60%-68%). Despite increasing evidence demonstrating that the HPV vaccine confers protection against vaginal, vulvar, and anal cancers, [3][4][5][6] most physicians in this survey were unaware of this additional protection. OB-GYNs were the best informed, with identification of noncervical cancer protection at least twice as often as other specialties, which is consistent with prior research.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] Correspondingly, a high level of vaccine efficacy, for the quadrivalent vaccine, has been demonstrated against infection and disease caused by HPV types 6, 11, 16 and 18. [1][2][3][4][5]34 Although an immune correlate of protection against HPV infection has not yet been established, understanding the limitations and benefits of various immunoassays will help inform and refine immunogenicity studies and shed light on the current tools, the ability of the current immunoassays, to distinguish an immune correlate of protection if breakthrough cases should be observed in the future.…”
Section: -26mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] These vaccines are composed of viruslike particles (VLPs), which are made by expressing the L1 major capsid protein of specific HPV types in eukaryotic cells. These types are: HPV types 6, 11, 16 and 18 in the quadrivalent vaccine (Gardasil ® ), and HPV types 16 and 18 in the bivalent vaccine (Cervarix TM ).…”
Section: Introductionmentioning
confidence: 99%
“…Randomized trials have shown that both the quadrivalent and bivalent HPV vaccines are highly efficacious in preventing HPV infection, cervical dysplasia, anal dysplasia and in the case of the quadrivalent vaccine, genital warts. [1][2][3][4][5] As part of the introduction of HPV vaccine globally, jurisdictions that started public programs were encouraged to embark on comprehensive monitoring programs to determine HPV vaccine safety, uptake, acceptability and impact of the program on HPV prevalence, cervical dysplasia and ultimately, cervical cancer. 6 Data from Australia, the United States and the United Kingdom have shown that the vaccine is effective, with population level reductions in rates of genital warts, HPV and cervical cancer lesions.…”
mentioning
confidence: 99%